Developing a Web-Based Basketball Court Booking Application (Baszone) Using Design Thinking - Anak Agung Adi Wiryya Putra; I Gde Suwastika Pande Liemena (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
This study designs Baszone, a web-based basketball court booking application developed through design thinking methodology. As basketball participation increases, manual reservation processes create significant obstacles for users and administrators. The research employed interviews with field administrators at DC Basketball in Denpasar, Bali, to identify operational challenges and user needs. Design thinking was implemented across five stages: empathize, define, ideate, prototype, and test. During empathize, interviews revealed booking difficulties including time-consuming manual processes and schedule conflicts. The define stage established user personas representing target audience characteristics. Ideate produced storyboards visualizing application workflows. Prototype development utilized Figma to create high-fidelity interface designs. Testing involved potential users evaluating the application through System Usability Scale (SUS) methodology. Results demonstrate that Baszone significantly enhances booking efficiency and accessibility. The application provides real-time field availability, streamlined reservation processes, and transparent payment management. SUS testing yielded a score of 92, indicating excellent usability performance. Respondents reported satisfaction with operational simplicity, optimal functionality, and comfortable interaction patterns. Baszone successfully addresses manual booking limitations while meeting user expectations for modern sports facility management systems.